Graduate school in the modern model of engineering education - V. . Senashenko; E. . Kon'Kova; S. . Vasilieva (Moscow Polytechnic University, 2022)
The article focuses on the problems concerning functioning of graduate school within the framework of modern engineering education system. Master's degrees programs are considered as a base for the development of individual educational trajectory and for solving the problem of individual preparation of engineerEresearchers. The authors discuss the different variants offorming the master's programs taking into account the conditions of functioning of twoeducational subsystems.